Comparative evaluation of three commercially available markerless depth sensors for close-range use in surgical simulation: original article - Burger, Lukas; Sharan, Lalith; Karl, Roger; Wang, Christina; Karck, Matthias; De Simone, Raffaele; Wolf, Ivo; Romano, Gabriele; Engelhardt, Sandy (International journal of computer assisted radiology and surgery, 2023)
Minimally invasive surgeries have restricted surgical ports, demanding a high skill level from the surgeon. Surgical simulation potentially reduces this steep learning curve and additionally provides quantitative feedback. Markerless depth sensors show great promise for quantification, but most such sensors are not designed for accurate reconstruction of complex anatomical forms in close-range.